2021
DOI: 10.1111/jfir.12235
|View full text |Cite
|
Sign up to set email alerts
|

Institutional monitoring and litigation risk: Evidence from employee disputes

Abstract: In this study, we investigate how institutional investors help mitigate businessrelated risks in a corporate environment. Using a large sample of employment disputes, litigations, and court cases, we find that institutional investors play a significant role in reducing employment litigation. We observe that firms with larger shares of institutional ownership have a lower incidence of employment lawsuits and that long-term institutional investors are more effective at decreasing employee mistreatment. Our resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Specially, pension funds and ESG/CSR performance (Dyck et al, 2019; Kim, Wan, et al, 2019; Oh et al, 2011) or reporting (Garcia‐Sanchez et al, 2020) are positively related. Rayfield and Unsal (2021) found that pension funds moderate the negative link between ownership ratio and employment lawsuits as an inverse measure of social performance. According to Cahan et al (2017), pension funds moderate the positive link between CSR performance and IO, and vice versa.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Specially, pension funds and ESG/CSR performance (Dyck et al, 2019; Kim, Wan, et al, 2019; Oh et al, 2011) or reporting (Garcia‐Sanchez et al, 2020) are positively related. Rayfield and Unsal (2021) found that pension funds moderate the negative link between ownership ratio and employment lawsuits as an inverse measure of social performance. According to Cahan et al (2017), pension funds moderate the positive link between CSR performance and IO, and vice versa.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
“…Prior studies have found supportive results for this argument. Regarding ESG/CSR, two Indian studies (Manogna & Mishra, 2020; Yadav, 2020) and one US study (Rayfield & Unsal, 2021) stressed a positive impact on mutual funds. According to Rayfield and Unsal (2021), mutual funds moderate the negative link between IO ratio and employment lawsuits as an inverse measure of social performance.…”
Section: Findings Of the Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Markets are growing increasingly hostile towards firms that produce non-green innovation or actively produce excess greenhouse gases. Firms can experience pressure to produce a more equitable environment from several stakeholders, including state and local governments, consumers, employees (Rayfield and Unsal, 2021) and institutional investors (Cheng et al , 2020).…”
Section: Literature Review and Ethical Debatementioning
confidence: 99%
“…Second, institutional investors’ professional business analysis ability and information capturing ability can correct the CEO decision-making bias caused by information asymmetry, effectively restrain the CEO earnings management behavior and weaken the company’s information risk. Finally, the higher the shareholding ratio of institutional investors, the greater the enthusiasm to supervise listed companies and the more likely to take measures to interfere with the company’s violations (Lu et al , 2012), which can reduce the litigation risk (Rayfield and unsal, 2021). In summary, the high shareholding ratio of institutional investors will further promote the inhibitory effect of CEO hometown identity on company’s agency risk, information risk and litigation risk, which in turn reinforces the negative effect of CEO hometown identity on audit fees.…”
Section: Heterogeneity Analysismentioning
confidence: 99%